PENGARUH PENGGUNAAN SISTEM TEKNOLOG INFORMASI DAN PERSEPSI MITRA KERJA (SATKER) TERHADAP MODUL PENERIMAAN NEGARA GENERASI KE II (MPN G2) PADA KPPN MAKASSAR II - Indrawan Azis (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
The Title of this research is “Information Technology System Influence and Partnership Perception to 2nd Generation Nation Reception Module (MPN G2) of KPPN Makassar II”, The Information Technology System development is also take effect on Government that more and more attempted to optimize the Information Technology System, as example to develop Tax Payment System in online known as 2nd Generation Nation Reception Module (MPN G2). The Focus of this research is not only to compare usage of MPN G1 and MPN G2, but also to identify KPPN Makassar II Partnership Perception of MPN G2 that just been applicated on 2016. Data Analysis Method of this research is qualitative analysis consist of validity test, reliability test, and multiple linear regression analysis. Data analysis process is obtain by SPSS version 17, From the resullt of data, it prove that the Information Technology System’s effect and partnership perception giving positive and significant influences to KPPN Makassar II by MPN G2